2019
DOI: 10.1177/0284185119830282
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of renal angiomyolipoma without visible fat from renal cell carcinoma by machine learning based on whole-tumor computed tomography texture features

Abstract: Background Morphological findings showed poor accuracy in differentiating angiomyolipoma without visible fat (AMLwvf) from renal cell carcinoma (RCC). Purpose To determine the performance of a machine learning classifier in differentiating AMLwvf from different subtypes of RCC based on whole-tumor slices of CT images. Material and Methods In this retrospective study, 171 pathologically proven renal masses were collected from a single institution. Texture features were extracted from whole-tumor images in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 33 publications
1
38
1
Order By: Relevance
“…However, up to 5% of AMLs lack macroscopic fat, a condition known as AML without visible fat (AMLwvf), making it challenging to differentiate them from RCC by conventional imaging [36]. Several studies described certain imaging features that are highly suggestive of AMLwvf and analyzed them with radiomics models [20][21][22][23]25,26].…”
Section: Angiomyolipoma (Amlwvf) Vs Rcc Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, up to 5% of AMLs lack macroscopic fat, a condition known as AML without visible fat (AMLwvf), making it challenging to differentiate them from RCC by conventional imaging [36]. Several studies described certain imaging features that are highly suggestive of AMLwvf and analyzed them with radiomics models [20][21][22][23]25,26].…”
Section: Angiomyolipoma (Amlwvf) Vs Rcc Subtypesmentioning
confidence: 99%
“…Other investigations employed similar strategies, although with ML-based TA from CECT images, and they reported higher accuracy (93.9%) and AUC (0.955) [21,24]. Moreover, Cui et al proposed an automatic computer identification system to differentiate AMLwvf from all RCC subtypes from whole-tumor CECT images using an over-sampling technique to increase the sample volume of AMLwvf [23]. They showed that morphological interpretation by radiologists achieved overall lower performance differentiating AMLwvf from all RCC subtypes.…”
Section: Angiomyolipoma (Amlwvf) Vs Rcc Subtypesmentioning
confidence: 99%
“…Even if data preprocessing was carried out with standardization, normalization, and et al, the classifiers, such as linear SVC, Multinomial-Naïve-Bayes and AdaBoost didn't perform better. The RFECV method worked well in other fields, such as image processing, financial data analyzing, and was already used in medical research [25,26]. The classifiers used in the study; except ExtraTrees, RandomForest and the simple deep learning model, didn't work well (with highest accuracy of 0.815) to subtype ischemic stroke (IS) with 8 neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…First, it allows one to massively scale the process of kidney segmentation in cross-sectional imaging compared to manual segmentation, which is precursor to any analysis that requires segmented tumor volumes. [11,[20][21][22][23] Perhaps more importantly, it can serve as an important infrastructural component for methods that aim to predict clinical attributes, such as pathologic features, from cross-sectional imaging. [10] The present results represent foundational work for the more ambitious goal of developing deep learning methods to enhance clinical diagnosis from radiologic images.…”
Section: Discussionmentioning
confidence: 99%